2015
DOI: 10.3389/fmicb.2015.00743
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of multi-drug resistant Acinetobacter baumannii population in a major hospital in Kuwait

Abstract: Acinetobacter baumannii is one of the most important opportunistic pathogens that causes serious health care associated complications in critically ill patients. In the current study we report on the diversity of the clinical multi-drug resistant (MDR) A. baumannii in Kuwait by molecular characterization. One hundred A. baumannii were isolated from one of the largest governmental hospitals in Kuwait. Following the identification of the isolates by molecular methods, the amplified blaOXA-51-like gene product of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
6
21
0
Order By: Relevance
“…KT346360]) identified in clinical A. baumannii isolates recovered prior to 2010 in Australia (26), was excluded. ISAba19 is an A. baumannii-original insertion sequence with a length of 1,309 bp, which was found inserted into the bla OXA-78 gene in clinical A. baumannii isolates (27). Additionally, pRCH52-1 harbors a tetA(39)-tetR(39) unit (1,895 bp); the original study showed that tetA(39) was located on a plasmid from A. baumannii isolated in 1997, but only a 3,727-bp fragment was sequenced (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…KT346360]) identified in clinical A. baumannii isolates recovered prior to 2010 in Australia (26), was excluded. ISAba19 is an A. baumannii-original insertion sequence with a length of 1,309 bp, which was found inserted into the bla OXA-78 gene in clinical A. baumannii isolates (27). Additionally, pRCH52-1 harbors a tetA(39)-tetR(39) unit (1,895 bp); the original study showed that tetA(39) was located on a plasmid from A. baumannii isolated in 1997, but only a 3,727-bp fragment was sequenced (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that all the isolated strains were susceptible to tigecycline and colistin. However, there have been many reports of tigecycline and colistin resistance, which range from 0.6% to 45.8% [18][19][20][21] and 0 to 30.6%, respectively, around the world [22][23][24][25]. Furthermore, colistin resistance was reported to be of 4% in the EARS-Net 2016 report [26].…”
Section: Discussionmentioning
confidence: 99%
“…ST158 isolates were also reported in Lebanon between 2011 and 2013 [42]. The recognition of Ab-Pak-cluster-7 in Pakistan has then expanded the geographic distribution of ST158 beyond the Middle East [43][44][45][46].…”
Section: Ab-pak-cluster-7 a New Member Of Clone St158mentioning
confidence: 99%